Effect of Organic and Conventional Nutrient Management on Growth and Yield of Broad Leaf Mustard (Brassica juncea var. rugosa) - Bhattarai, B.P.; Singh, K.P.; Shakya, S.M.; Khatri-Chhetri, G.B.; Khadka, Y.G. (Nepalese Horticulture, 2018)
Abstract available with the full text.